2019
DOI: 10.1089/scd.2019.0102
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Hydrogels for the Local Delivery of Mesenchymal Stromal Cells to the Injured Vocal Fold

Abstract: You have the right to do your actions, but you should not worry about the results (Bhagavad Gita, Chapter 2-Stanza 47)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 242 publications
(264 reference statements)
0
19
0
Order By: Relevance
“…An excellent safety profile is in line with results from intravenous (IV) MSC administration [13,14]. We could not analyze engraftment or survival of the administered MSCs within this trial for ethical reasons, but in animal models, MSC mode of action has been demonstrated to be via a "hit and run" effect, with few cells persisting within the VF tissue over 1 month after injection [18][19][20][21][22][23]. VF scarring is a condition resulting in severe voice problems for which lasting effective treatment has been elusive.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…An excellent safety profile is in line with results from intravenous (IV) MSC administration [13,14]. We could not analyze engraftment or survival of the administered MSCs within this trial for ethical reasons, but in animal models, MSC mode of action has been demonstrated to be via a "hit and run" effect, with few cells persisting within the VF tissue over 1 month after injection [18][19][20][21][22][23]. VF scarring is a condition resulting in severe voice problems for which lasting effective treatment has been elusive.…”
Section: Discussionmentioning
confidence: 86%
“…We have furthermore confirmed the safety and effectiveness of delivering MSCs within HA hydrogel in vivo. These findings provided us with data supporting that HA could be safely used as a delivery vehicle where defects were of a critical size, providing a scaffold for the MSCs [23].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations